Implementation of Environmentally Friendly Policie at Indonesian Crossing Ports: A Literature Study - Setiawan, A A; Suharto, D G (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
This research describes sustainable environmentally friendly policies of all operations that are able to adapt to world changes. This paper aims to analyze stakeholder policies in realizing an environmentally friendly port from all operations, both on crossing ships, ports, and from a management perspective. The research method is qualitative with literature review and systematic literature review, the data used is secondary data. The data search was carried out based on national journals and international journals. The results is the study show that stakeholders through the ministry of transportation have taken a number of steps to create a better environment.